Nanocrystalline MgCrxAl2-xO4: Facile synthesis and thermal dependency of photoluminescence. (October 2017) - H.G., Shreekrishna Karthik; Menon, Samvit G.; Hebbar N., Deepak; Choudhari, K.S.; C., Santhosh; Kulkarni, Suresh D.
Graphical abstract: Highlights: Red emitting MgCrx Al2-x O4 Hexagonal sheet like nanoparticles synthesized. Annealing improved crystallinity and material turned pink at 1200 °C. The R-line was intense but sidebands are less pronounced than in ZnAl2 O4 host. High Dq/B confirm strong field relating PL with spin-parity forbidden transitions. The lifetimes ranged between 20 and 24 ms much higher than reports. Abstract: MgCrx Al2-x O4 nanoparticles were synthesized by facile co-precipitation method. The x = 0.02 sample showed intense emission and considered for studying the effect of annealing temperature (500–1200 °C) on the structural and optical properties. On annealing, crystallinity improved and the material gradually turned pink at 1200 °C. Hexagonal sheet-like nanoparticles (∼52 nm) were observed by HRTEM and the lattice fringes suggested their single crystalline nature. Excitation spectra showed two peaks at 546 and 419 nm where the latter was asymmetric, attributable to the trigonal distortion. The photoluminescence consisted of intense zero-phonon line and associated multi-phonon side bands, whose intensities increased with annealing. Higher Dq/B (3.5), confirmed strong crystal field for Cr 3+, suggesting that the photoluminescence emission could be associated with spin-parity forbidden transitions. The emission lifetimes (λem  = 688 nm) ranged between ∼20 and 24 ms. Other oxide nanoparticles suitable for phosphors, biomarkers, etc. can be conveniently synthesized similarly.